2020
DOI: 10.1093/ibd/izz335
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Gut Microbial Changes Predict RecurrentClostridiodes DifficileInfection in Patients With and Without Ulcerative Colitis

Abstract: Background Ulcerative colitis (UC) carries an increased risk of primary and recurrent Clostridiodes difficile infection (rCDI), and CDI is associated with UC flares. We hypothesized that specific fecal microbial changes associate with UC flare and rCDI. Methods We conducted a prospective observational cohort study of 57 patients with UC and CDI, CDI only, and UC only. Stool samples were collected at baseline, at the end of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…BBR could renovate the abundances of genus Adlercreutzia, Dorea, Sutterella and Plesiomonas and increase the abundance of Lactobacillus in GVHD mice. The abundance of these 5 kinds of genus was reported to be decreased in IBD or GVHD patient except Plesiomonas and re-introduction of some of them could improve the disease in previous studies, [27][28][29][30][31] which were mostly in consistent with our result.…”
Section: Discussionsupporting
confidence: 92%
“…BBR could renovate the abundances of genus Adlercreutzia, Dorea, Sutterella and Plesiomonas and increase the abundance of Lactobacillus in GVHD mice. The abundance of these 5 kinds of genus was reported to be decreased in IBD or GVHD patient except Plesiomonas and re-introduction of some of them could improve the disease in previous studies, [27][28][29][30][31] which were mostly in consistent with our result.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with ours and suggest MHI-A may have a role in predicting antibiotic response in CDI patients. A second study combined microbiome composition 14 days after CDI antibiotic treatment with patient clinical and demographic characteristics to predict CDI recurrence ( Lee et al, 2020 ). They found that increased Bacteroidetes, Lachnospiraceae , and Ruminococcaceae (Clostridia), and decreased Gammaproteobacteria correlated with reduced CDI recurrence, trends that are highly consistent with MHI-A.…”
Section: Discussionmentioning
confidence: 99%
“…The Dorea identified in this study belongs to the Lachnospiraceae family, which mainly exists in the gut microbiota of mammals and humans. One previous study has established a link between Lachnospiraceae and IBD ( Lee et al, 2020 ). Another recent studies has also confirmed that the level of Lachnospiraceae and butyric acid gets decreased in IBD patients ( Sasaki et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%